Composition and antifungal activity of essential oils from Piper aduncum, Piper arboreum and Piper tuberculatum - Navickiene, HMD; Morandim, ADA; Alecio, A. C.; Regasini, L. O.; Bergamo, DCB; Telascrea, M.; Cavalheiro, Alberto José [UNESP]; Lopes, Márcia Nasser [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP]; Marques, MOM; Young, MCM; et al. (Soc Brasileira Quimica, 2006)
The composition of essential oils from leaves, stems and fruits of Piper aduncum, P arboreum and P. tuberculatum was examined by means of GC-MS and alltifungal assay. There was a predominance of monoterpenes in P aduncum and P tuberculatum and of sesquiterpenes in P arboreum. P aduncum showed the richest essential oil composition, including linalool. The essential oils from fruits of P. aduncum and R tuberculatum showed the highest antifungal activity with the MIC of 10 mu g as determined against Cladosporium cladosponoides and C. sphaerospermum, respectively. This is the first report of the composition of essential oils from P. tuberculatum.
Keywords: Piper; essential oil composition; antifungal activity